The complete chloroplast genome sequence of Trapa bicornis Osbeck (Lythraceae) - Fangfang Sun; Yulai Yin; Bowen Xue; Ronghua Zhou; Jun Xu (Mitochondrial DNA. Part B. Resources, 2020)
Trapa (Lythraceae) is an aquatic plant genus widely distributed in the old world. Although Trapa species have great edible and medical value, studies related to species identification and utilization are still lacking. Here, we reported the complete chloroplast genome sequence of a cultivated species, T. bicornis. The chloroplast genome size of T. bicornis was 155,539 bp, consisting of a pair of inverted repeat (IR) regions (24,386 bp), separated by a large single copy (LSC) region (88,493 bp) and a small single copy (SSC) region (18,274 bp). A total of 130 genes were annotated, including 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenomic analysis supported the monophyly of Trapa, and a sister relationship between T. bicornis and T. natans.